High incidence of maternal vitamin B12 deficiency detected by newborn screening: first results from a study for the evaluation of 26 additional target disorders for the German newborn screening panel - Gramer, Gwendolyn; Fang-Hoffmann, Junmin; Klinke, Glynis; Monostori, Péter; Okun, Jürgen G.; Hoffmann, Georg F. (World journal of pediatrics, 2018)
Background: Newborn screening (NBS) in Germany currently includes 15 target disorders. Recent diagnostic improvements suggest an extension of the screening panel. Methods: Since August 2016, a prospective study evaluating 26 additional target disorders (25 metabolic disorders and vitamin B12-deficiency) in addition to the German screening panel is performed at the Newborn Screening Center Heidelberg. First-tier results from tandem-MS screening are complemented by second-tier strategies for 15 of the additional target disorders. NBS results of seven patients diagnosed symptomatically with one of the additional target disorders by selective screening since August 2016 are retrospectively evaluated. Results: Over a 13-month period, 68,418 children participated in the study. Second-tier analyses were performed in 5.4% of samples. Only 59 (0.1%) of study participants had abnormal screening results for one of the additional target disorders. Target disorders from the study panel were confirmed in 12 children: 1 3-hydroxy-3-methylglutaryl coenzyme A (CoA)-lyase deficiency, 1 citrullinemia type I, 1 multiple acyl-CoA dehydrogenase-deficiency, 1 methylenetetrahydrofolate reductase-deficiency, and 8 children with maternal vitamin B12-deficiency. In addition, six of seven patients diagnosed symptomatically outside the study with one of the target disorders would have been identified by the study strategy in their NBS sample. Conclusions: Within 13 months, the study “Newborn Screening 2020” identified additional 12 children with treatable conditions while only marginally increasing the recall rate by 0.1%. Maternal vitamin B12-deficiency was the most frequent finding. Even more children could benefit from screening for the additional target disorders by extending the NBS panel for Germany and/or other countries.
Gesehen am 15.05.2019
Im Titel ist die Zahl "12" tiefgestellt